Respuesta :

Hi1315

Answer:

x = 4

Step-by-step explanation:

3 ( x + 4 ) - 1 = 23

First solve the brackets.

3x + 12 - 1 = 23

3x + 11 = 23

Now take 11 to the other side n solve it.

3x = 23 - 11

3x = 12

Now divide both sides by  3.

3x/3 = 12/3

x = 4

Hope this helps you :-)

Let me know if you have any other questions :-)

Have a nice day !!!

Answer:

3(x+4)-1+1=23+1

add 1 to both sides

3(x+4)=24

divide both sides by 3

[tex]\frac{3(x+4)}{3} =\frac{24}{3}[/tex]

x+4=8

x+4-4=8-4

subtract 4 from both sides

x=4

Step-by-step explanation:

ACCESS MORE